Collecting a Poultry Litter Sample for Analysis - George J. Hochmuth; Justine T. Jones (EDIS)
Through research, tables have been developed that describe the average nutrient concentration of animal wastes. However, the actual nutrient concentration of manures may vary from one livestock operation to another. Factors that contribute to this variation include: composition of the feed ration, design of the waste management system, season of year, animal health, etc. Therefore, it is important that livestock wastes are sampled and analyzed to determine their nutrient concentrations before a sound, nutrient management plan can be designed, implemented, or maintained. This document is HS938, one of a series of Department of Horticultural Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. November 2003.